2002
DOI: 10.1523/jneurosci.22-07-02956.2002
|View full text |Cite
|
Sign up to set email alerts
|

Completing the Corticofugal Loop: A Visual Role for the Corticogeniculate Type 1 Metabotropic Glutamate Receptor

Abstract: The way in which the brain deals with sensory information relies not only on feedforward processing of signals from the periphery but also on feedback inputs. This is the case of the massive projection back from layer 6 in the visual cortex to the thalamus, for which, despite being the greatest single source of synaptic contacts, the functional role still remains unclear. In the cat lateral geniculate nucleus, part of this cortical feedback is mediated by type 1 metabotropic glutamate receptors (mGluR1s), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
(56 reference statements)
1
51
0
Order By: Relevance
“…In comparison with retinal ganglion cells, LGN cells are known to exhibit lower background and stimulus-driven firing, nonlinear changes in contrast gain and spatial properties, and enhanced center surround antagonism (44)(45)(46)(47)(48). The feedback projection to the LGN has been shown to be involved in these effects (14,(49)(50)(51). Additionally, both the temporal response profile (8,52) and information transfer (10), as well as non-stimulus-locked synchrony (11), are known to be modified by cortical feedback.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with retinal ganglion cells, LGN cells are known to exhibit lower background and stimulus-driven firing, nonlinear changes in contrast gain and spatial properties, and enhanced center surround antagonism (44)(45)(46)(47)(48). The feedback projection to the LGN has been shown to be involved in these effects (14,(49)(50)(51). Additionally, both the temporal response profile (8,52) and information transfer (10), as well as non-stimulus-locked synchrony (11), are known to be modified by cortical feedback.…”
Section: Discussionmentioning
confidence: 99%
“…In the cat lateral geniculate nucleus, cortical feedback is partly mediated by type 1 metabotropic glutamate receptors, which are located exclusively on distal segments of the relay-cell dendrites. Rivadulla, Martinez, Varela, and Cudeiro (2002) have shown that these backward afferents enhance the excitatory centre of the thalamic receptive field. "Therefore, cortex, by closing this corticofugal loop, is able to increase the gain of its thalamic input within a focal spatial window, selecting key features of the incoming signal" (Rivadulla et al, 2002).…”
Section: Hierarchical Organisationmentioning
confidence: 99%
“…There seems to be little evidence for a contribution to sensory responses of additional glutamate receptors from in vitro physiological studies, even though experiments have been designed that have attempted to reveal roles for, for example, metabotropic glutamate receptors (Turner & Salt 1998). By contrast, the situation appears to differ in in vivo experiments, where there appear to be sensory responses that have a contribution from mGlu receptors, and it is prob- 2002) able that this re ects recruitment of additional circuitry, possibly corticothalamic inputs (see § 3) (Eaton et al 1993;Salt & Turner 1998b;Rivadulla et al 2002).…”
Section: Sensory Inputs To Thalamic Relay Nucleimentioning
confidence: 99%
“…This may not be the case in all situations. However, using certain natural somatosensory or visual stimuli which may appropriately activate cortical areas in vivo it has been shown that thalamic responses to sensory stimuli are reduced in the presence of mGlu1 antagonists in both VB ( gure 3) (Salt & Turner 1998b) and the LGN ( gure 4) (Rivadulla et al 2002), and this may re ect activation of the cortical input to the thalamic relay neurons. A feature of some of these stimuli is that they are of a sustained nature, and it may be the case that this is critical to (Rivadulla et al 2002).…”
Section: Sensory Responses Of Thalmic Relay Neurons In Vivo: Recruitmmentioning
confidence: 99%
See 1 more Smart Citation